Cells, scaffolds, and bioactive factors: Engineering strategies for improving regeneration following volumetric muscle loss - Eugenis, Ioannis; Wu, Di; Rando, Thomas A. (Biomaterials, 2021)
Severe traumatic skeletal muscle injuries, such as volumetric muscle loss (VML), result in the obliteration of large amounts of skeletal muscle and lead to permanent functional impairment. Current clinical treatments are limited in their capacity to regenerate damaged muscle and restore tissue function, promoting the need for novel muscle regeneration strategies. Advances in tissue engineering, including cell therapy, scaffold design, and bioactive factor delivery, are promising solutions for VML therapy. Herein, we review tissue engineering strategies for regeneration of skeletal muscle, development of vasculature and nerve within the damaged muscle, and achievements in immunomodulation following VML. In addition, we discuss the limitations of current state of the art technologies and perspectives of tissue-engineered bioconstructs for muscle regeneration and functional recovery following VML.